Advances in the Catalytic Reductive Amination of Furfural to Furfural Amine: The Momentous Role of Active Metal Sites. Issue 7 (7th March 2022) - Saini, Ms. Kanika; Kumar, Sahil; Li, Hu; Babu, Srinivasarao Arulananda; Saravanamurugan, Shunmugavel
Abstract: One‐pot synthesis of sustainable primary amines by catalytic reductive amination of bio‐based carbonyl compounds with NH3 and H2 is emerging as a promising and robust approach. The primary amines, especially furfuryl amine (FUA) derived from furfural (FUR), with a wide range of applications from pharmaceuticals to agrochemicals, have attracted much attention due to their versatility. This Review is majorly comprised of two segments on the reductive amination of FUR to FUA, one with precious (Ru, Pd, Rh) and the other with non‐precious (Co, Ni) metals on different supports and in various solvent systems in the presence of NH3 and H2 . The active metal sites generated on multiple supports are accentuated with experimental evidence based on CO‐diffuse reflectance infrared Fourier‐transform spectroscopy, H2 temperature‐programmed reduction, X‐ray photoelectron spectroscopy, and calorimetry. Moreover, this Review comprehensively describes the role of acidic and basic support for the metal on the yield of FUA. Overall, this Review provides an insight into how to design and develop an efficiently robust catalyst for the selective reductive amination of a broad spectrum of carbonyl compounds to corresponding amines. Abstract : Reductive amination : This Review provides an overview of understanding the active catalytic species of various metal‐supported materials employed for the reductive amination of furfural to furfuryl amine in aqueous and organic solvents in the presence of H2 and ammonia sources and emphasizes the importance of unique characterization techniques that help in understanding active catalytic species.